Dual‐view holographic AR display based on Bragg mismatched reconstruction of the holographic optical element. Issue 1 (14th December 2022) - Qin, Xiujuan; Sang, Xinzhu; Li, Hui; Xiao, Rui; Zhong, Chongli; Yan, Binbin; Sun, Zhi; Dong, Yu
Abstract: A method for dual‐view holographic display based on Bragg mismatched reconstruction of holographic optical element (HOE) is proposed. Under the Bragg mismatched condition, the reconstructed images are guided into two separated viewing zones to realize dual‐view holographic display. Meanwhile, the viewing angle of each perspective is increased to 11.2°, which is almost 2.5 times as large as the traditional holographic display system. The design process of HOE is simple only by interference of plane reference wave and converging spherical signal wave, which has high practicability. Furthermore, the HOE can mix the virtual 3D image with real‐world scenes, which could implement augmented reality (AR) display. Experiments validate that the proposed system can achieve dual‐view holographic AR three‐dimensional (3D) display with accommodation effect. Abstract : We designed a dual‐view holographic AR 3D display system based on the Bragg mismatched reconstruction of holographic optical element. The viewing angle of each perspective is enhanced to 11.2°, which is almost 2.5 times as large as the traditional holographic display system. The system can achieve dual‐view holographic AR 3D display with accommodation effect.